( الدرسُ الـبـلاغيّ والفـلـسـفـةُ الـعـربـيـةُ ) - طـارق فــرج عــلــي مــحــمــد الواحــدي (Aljameai, 1970)
المستخلص:إن ارتباط الفلسفة العربية بعلم البلاغة، يعد أمرا جديرا بالبحث والتقصي فهما علمان جليلان من أهم ركائز الحضارة العربية آنذاك، ويهدف العمل البحثي  إلى تتبع بدايات ارتباط الفلسفة العربية بالبلاغة، منذ اشتغال المتكلمين من علماء المعتزلة والأشاعرة بهذا العلم، كما يهدف  إلى النظر في كتاب سر الفصاحة للعالم الجليل ابن سنان الخفاجي، الذي أظهرت تحليلاته ارتباطا كبيرا بالفلسفة من خلال تعريفاته وشروحاته، وقد اتبع الباحث في عمله هذا المنهج الوصفي التحليلي، بوصفه للظاهرة كما وكيفا من خلال مدخل تأريخي، وتحليله لرؤى وأفكار وفلسفات الخفاجي من خلال كتابه سر الفصاحة.Abstract:                                                                                                             The connection between the Arabic philosophy and the study of rhetoric is considered as major material for research and Inquire for they are significant studies and are of the most grounds of the Arabic civilization at the time. And the research work aims to go after the very beginning of this engagement between the Arabic philosophy and the rhetoric, since the concerned speakers of the scientists of the Ash'ara and the Mu'tazila about this science, it's also aims to look closely in the book of Ser Al fsaha The Secret Of The Eloquence for the scientist Al Jalil Ibn Sinan Al Khajaji, whose his analyses showed a huge attachment with Philosophy through his definitions and explanations, and that's how the researcher followed in his research this descriptive analytical method, with describing this phenomenal with quantity and quality through Historical entrance, and analysing the visions and thoughts as well as the philosophies of Khajaji through his book Ser A lfsaha The Secret Of The Eloquence